Correlation Between Knowledge Level and Iron Tablet Consumption Behavior and the Incidence of Anemia Among Third Trimester Pregnant Women at PMB Nurasmalinda, Simpang Kiri District, Subulussalam, 2024 - Astaria Br Ginting; Suci Ramadayati; Dessy Ratna Sari Sembiring; Ninsah Mandala Putri Br Sembiring; Rolasnih Lilista Simbolon; Kamelia Sinaga (Cattleya Darmaya Fortuna, 2025)
Anemia during pregnancy remains a major public health issue, particularly in the third trimester when the risk to both mother and fetus increases. This study aims to determine the relationship between knowledge level and iron tablet consumption behavior with the incidence of anemia in third-trimester pregnant women at PMB Nurasmalinda, Simpang Kiri District, Subulussalam City, in 2024. This research uses an analytic survey method with a cross-sectional approach. A total of 35 third-trimester pregnant women were selected as respondents using total sampling. Data were collected through questionnaires and hemoglobin (Hb) level measurements. The results showed that 57.1% of respondents had low knowledge and 62.9% exhibited poor iron tablet consumption behavior. Bivariate analysis using the chi-square test revealed a significant relationship between knowledge level (p = 0.002) and consumption behavior (p = 0.001) with the incidence of anemia. Furthermore, multivariate analysis using logistic regression indicated that consumption behavior was the most influential factor (p = 0.008; OR = 4.77; 95% CI = 1.516–15.686). It can be concluded that iron tablet consumption behavior is a dominant factor in the incidence of anemia among third-trimester pregnant women. Health education and consistent monitoring are needed to improve knowledge and adherence to iron supplementation.